2004
DOI: 10.1021/ac0499423
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Saikosaponin Derivatives in Radix bupleuri and in Pharmaceuticals of the Chinese Multiherb Remedy Xiaochaihu-tang Using Liquid Chromatographic Tandem Mass Spectrometry

Abstract: Saikosaponins are bioactive oleanane saponins derived from the Chinese medicinal herb Radix bupleuri ("chaihu" in Chinese). An LC-MS/MS-based method has been developed for characterization and quantification of 15 saikosaponin derivatives (saikosaponin a, saikosaponin b(1), saikosaponin g, saikogenin A, saikogenin H, saikosaponin c, saikosaponin h, saikosaponin i, prosaikogenin C(2), prosaikogenin B(2), saikogenin C, saikogenin B, saikosaponin d, saikosaponin b(2), and saikogenin D) in one chromatographic run.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
71
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 47 publications
3
71
1
Order By: Relevance
“…We found that the concentration of HCOONH 4 had only negligible effects on the chromatographic peak widths, peak asymmetry, and peak retention times. Furthermore, a mobile phase containing 0.01‰ HCOONH 4 resulted in minimal matrix effects for all of the tested flavonoids.…”
Section: Lc-ms/ms Detection Of the Tested Licorice Flavonoidsmentioning
confidence: 77%
See 3 more Smart Citations
“…We found that the concentration of HCOONH 4 had only negligible effects on the chromatographic peak widths, peak asymmetry, and peak retention times. Furthermore, a mobile phase containing 0.01‰ HCOONH 4 resulted in minimal matrix effects for all of the tested flavonoids.…”
Section: Lc-ms/ms Detection Of the Tested Licorice Flavonoidsmentioning
confidence: 77%
“…Electrospray ionization was used to efficiently generate precursor deprotonated molecules of all the analytes and the [M-H] Ϫ ions were used to produce characteristic product ions for MS/MS analysis. We found that inclusion of a very low concentration of HCOONH 4 (0.01‰) in the LC mobile phase dramatically improved the detection limit for the tested flavonoids and decreased the interference by matrix effects, which have been referred to as "LC-electrolyte effects." Liquid-liquid extraction with ethyl acetate was effective for isolation of all the analytes and resulted in the lowest matrix effects of several tested sample cleanup methods.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…HPLC with a mass spectrometer detector (LC-MS) [39,40] showed superior sensitivity and selectivity compared to HPLC-UV methods [41].…”
Section: Detectionmentioning
confidence: 99%